Intracellular Proteinase a Activities and Gene Expression of Isolated Candida Species in Malaysian and Iranian Patients - Saroukolaei, Shahla Amri (2011)
Intracellular aspartic proteinase A is an important enzyme in Candida species.The main aim in this project was the comparison of the proteinase A activity in clinical isolates and control Candida species isolated from immunocompromised and immunocompetent human patients among Malaysians and Iranians. The aim of this study was achieved through the purification of proteinase A to measure enzyme activity and also the evaluation of proteinase A gene expression (APR1) to assess gene activity in vitro and in vivo conditions in four species of Candida: C. albicans, C. tropicalis, C.parapsilosis and C. krusei. In this thesis the proteinase A activity in both systemic and non-systemic Candida spp were evaluated in three situations: isolated from human patients, mouse blood and mouse kidney. Purification of proteinase A was performed in two stages of ion-exchange and affinity chromatography by using DEAE-Cellulose and CON-A, respectively. The results showed that proteinase A activity in the three situations mentioned above in both the clinical and control isolates was higher in C. albicans than in non-albicans Candida species in Malaysian as well as Iranian samples (p<0.05). In the samples isolated from human patients, proteinase A activity in Malaysian samples both from systemic and non-systemic were significantly higher than in Iranian samples (p<0.05). This result was not observed in the samples obtained from mice blood and kidney (p>0.05). Reverse-transcriptase Polymerase Chain Reaction (RT-PCR) was done to determine APR1 gene expression with 18SrRNA as the house-keeping gene. From three groups of Candida spp mentioned above, APR1 gene expression in C. albicans was significantly higher than in non-albicans Candida in both Malaysians and Iranians (p<0.05). When comparing all Candida spp isolated in Malaysians against Iranians, APR1 gene expression in Candida spp isolated from Malaysian patients was significantly higher than in Iranian (p<0.05) unlike the Candida spp isolated from mouse blood and mouse kidney (p>0.05). The data demonstrated that systemic and non-systemic Candida spp had similar activity in the gene expression after injection into mice (p>0.05), while the activity before injection into mice was different so that systemic Candida spp had higher gene expression than non-systemic (p<0.001). The overall results obtained from this study showed that proteinase A activity and APR1 gene expression in clinical isolates and control Candida spp obtained from human patients were different between samples from Malaysia and Iran. After injecting Candida spp into mice, no significant difference in proteinase A between Malaysian and Iranian were seen, because environmental conditions for all Candida spp cells in the mouse host were almost similar. For C. albicans there was a significant difference with non-albicans Candida in enzyme activity and gene expression in both conditions of before and after injection of the Candida spp into mice. However, although proteinase A is not considered a virulence enzyme in Candida spp, it has an association with virulence enzymes in Candida cell defence, and the results of this study suggest that with an increased gene expression and activity, this enzyme can act as an important intracellular enzyme in different environmental situations.